Candid conversations with towering persons - Bhanumathy, K.P. (New Delhi National Book Trust, India, 2007)
Collection of interviews with 20th century national and international personalities.
Keywords: Bhanumathy, K.P. -- Interviews; Celebrities -- Interviews